Design, synthesis and bioactivity of myricetin derivatives for control of fungal disease and tobacco mosaic virus disease. Issue 10 (23rd February 2023) - Cao, Xiao; He, Bangcan; Liu, Fang; Zhang, Yuanquan; Xing, Li; Zhang, Nian; Zhou, Yuanxiang; Gong, Chenyu; Xue, Wei
Abstract : A series of myricetin derivatives containing isoxazole were designed and synthesized to control fungal disease and TMV disease. Abstract : A series of myricetin derivatives containing isoxazole were designed and synthesized. All the synthesized compounds were characterized by NMR and HRMS. In terms of antifungal activity, Y3 had a good inhibitory effect on Sclerotinia sclerotiorum (Ss), and the median effective concentration (EC50 ) value was 13.24 μg mL −1, which was better than azoxystrobin (23.04 μg mL −1 ) and kresoxim-methyl (46.35 μg mL −1 ). Release of cellular contents and cell membrane permeability experiments further revealed that Y3 causes the destruction of the cell membrane of the hyphae, which in turn plays an inhibitory role. The anti-tobacco mosaic virus (TMV) activity in vivo showed that Y18 had the best curative and protective activities, with EC50 values of 286.6 and 210.1 μg mL −1 respectively, the effect was better than ningnanmycin. Microscale thermophoresis (MST) data showed that Y18 had a strong binding affinity with tobacco mosaic virus coat protein (TMV-CP), with a dissociation constant ( K d ) value of 0.855 μM, which was better than ningnanmycin (2.244 μM). Further molecular docking revealed that Y18 interacts with multiple key amino acid residues of TMV-CP, which may hinder the self-assembly of TMV particles. Overall, after the introduction of isoxazole on the structure of myricetin, its anti-Ss and anti-TMV activities have been significantly improved, which can be further studied.